Methane Hydration‐Shell Structure and Fragility. Issue 46 (18th October 2018) - Wu, Xiangen; Lu, Wanjun; Streacker, Louis M.; Ashbaugh, Henry S.; Ben‐Amotz, Dor
Abstract: The influence of oily molecules on the structure of liquid water is a question of importance to biology and geology and many other fields. Previous experimental, theoretical, and simulation studies of methane in liquid water have reached widely conflicting conclusions regarding the structure of hydrophobic hydration‐shells. Herein we address this question by performing Raman hydration‐shell vibrational spectroscopic measurements of methane in liquid water from −10 °C to 300 °C (at 30 MPa, along a path that parallels the liquid‐vapor coexistence curve). We show that, near ambient temperatures, methane's hydration‐shell is slightly more tetrahedral than pure water. Moreover, the hydration‐shell undergoes a crossover to a more disordered structure above ca. 85 °C. Comparisons with the crossover temperature of aqueous methanol (and other alcohols) reveal the stabilizing influence of an alcohol OH head‐group on hydrophobic hydration‐shell fragility. Abstract : The shape of water : The influence of methane on the structure of liquid water is elucidated using Raman hydration‐shell vibrational spectroscopic measurements. Near ambient temperatures, methane's hydration‐shell is found to be slightly more tetrahedral than pure water, and then at higher temperatures it undergoes a crossover to a more disordered structure.